2017
DOI: 10.1002/ajhb.22966
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of skeletal maturity assessed by radiological and ultrasonic methods

Abstract: Objectives: The estimation of skeletal maturity is a useful tool in paediatric practice to determine the degree of delay or advancement in growth disorders and the effectiveness of treatment in conditions that influence linear growth. Skeletal maturity of children is commonly assessed by using either Greulich-Pyle (GP) or Tanner-Whitehouse methods (TW2 and TW3). However, a less invasive ultrasonic method, that does not use ionizing radiation, has been suggested for use in epidemiological studies of skeletal ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…The prospect of a bone agebased pubertal maturity assessment paradigm for research is enhanced by a non-invasive ultrasonic version of this method that scans the ossification of the wrist region to estimate bone age 29 . We have shown that ultrasonic bone age estimations of the wrist very strongly correlate with X-ray estimations 30 (r>0. 95), and therefore provide a promising tool to replace subjective, invasive, risky or costly assessments of maturity.…”
Section: Mainmentioning
confidence: 81%
See 1 more Smart Citation
“…The prospect of a bone agebased pubertal maturity assessment paradigm for research is enhanced by a non-invasive ultrasonic version of this method that scans the ossification of the wrist region to estimate bone age 29 . We have shown that ultrasonic bone age estimations of the wrist very strongly correlate with X-ray estimations 30 (r>0. 95), and therefore provide a promising tool to replace subjective, invasive, risky or costly assessments of maturity.…”
Section: Mainmentioning
confidence: 81%
“…After body height (DKSH anthropometer, Switzerland Ltd, Zurich, Switzerland) and body weight (Seca digital scale) measurements, we assessed skeletal maturity (bone age) with an ultrasonic device (Sunlight BonAge, Sunlight Medical Ltd, Tel Aviv, Israel). Ultrasonic testing prevents children from being exposed to radiation in contrast to earlier, X-ray based methods, and at the same time, ultrasonic estimations highly correlate with X-ray estimations 30 . These features make ultrasonic screening optimal for research purposes.…”
Section: Bone Age Assessmentmentioning
confidence: 95%
“…Biological age was estimated from bone age with an ultrasound-based device (Sunlight Medical Ltd., Tel Aviv, Israel). This method estimates the developmental stage of the skeleton and was shown to have high a reliability in boys up to 16 years and in girls up to 15 years [ 23 ]. Although the examination covers only a few bones, it can give a comprehensive assessment of the development of the skeletal system and can be used as an overall indicator of biological development [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have also been validating ultrasound and dual-energy X-ray absorptiometry (DEXA) to estimate skeletal age. These alternatives expose the subject to lower and non-ionizing radiation compared to X-ray radiography 39 , 40 ; however, those alternatives require sophisticated equipment at a high cost, which render its use less attractive in epidemiological studies.…”
Section: Discussionmentioning
confidence: 99%